Pattern of common skin diseases among school going children in Semi-Urban Area of Jaipur: A cross-sectional study - Manisha Nijhawan; Manmohan Bagri; Shivi Nijhawan; Subhash Bishnoi; Savita Agarwal; Sandeep Nijhawan (Wolters Kluwer Medknow Publications, 2020)
Aims: Skin disorders are a common health problem in pediatric age group, and a school-based survey seems to be a good screening tool for estimating the prevalence of cutaneous disorders among children. Subjects and Methods: A cross-sectional prospective study was conducted in three schools of semi-urban area of Jaipur. A total of 576 children including 218 boys and 358 girls of age group 4-18 years were examined for the study, and laboratory investigations were also done for all the children. Results: Out of 576 students, 349 students were found to have a skin disorder. Of all the affected children, 69.7% (370) had noninfectious dermatoses, 19.8% (105) had infectious dermatoses, and 10.5% (56) had nutritional dermatoses. Conclusions: In our study, the prevalence of skin infection was found to be associated with low socioeconomic status and poor personal hygiene. Hence, awareness regarding skin-related health problems in children as well as in their parents seems to be of utmost importance.